Characterization of the Intermediate in and Identification of the Repair Mechanism of (6‐4) Photolesions by Photolyases. Issue 17 (21st March 2016) - Faraji, Shirin; Zhong, Dongping; Dreuw, Andreas
Abstract: Quantum mechanics/molecular mechanics calculations are employed to assign previously recorded experimental spectroscopic signatures of the intermediates occurring during the photo‐induced repair of (6‐4) photolesions by photolyases to specific molecular structures. Based on this close comparison of experiment and theory it is demonstrated that the acting repair mechanism involves proton transfer from the protonated His365 to the N3′ nitrogen of the lesion, which proceeds simultaneously with intramolecular OH transfer along an oxetane‐like transition state. Abstract : QM/MM simulations were conducted to assign a specific molecular structure to the intermediate formed in the electron‐induced repair of (6‐4) photolesions (purple) detected previously in ultrafast transient absorption spectroscopy. The repair mechanism involves proton transfer from the protonated His365 to the N3′ nitrogen of the lesion along an oxetane‐like transition state.